Book Review: Against Liberalism, on a Repercussive Critics on Liberalism - Hamid Malekzadeh; Ahmad Khaleghi damghani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this essay, we have tried to study the form and content of the book Against Liberalism, to show that John Kekes’s work is suffering from a kind of theoretical trap that runs throughout his book. In doing so, we have followed a textualist standpoint by which we aimed to highlight the main framework of Kekes’s understanding of liberalism. We explained that his understanding of liberalism is fundamentally affected by his conservatism standpoint. This affection is the main source of what we call Kekes’s theoretical trap. The theoretical trap that ultimately leads the author to a misunderstanding on his goal, which is to present a coherent critique of liberalism, and turns his work into rhetorical statements in political debates. We have tried, as far as possible, to refrain from using any personal views on politics in this paper, especially in the face of liberalism and conservatism. John Kekes’s book is, in general, and in terms of scientific validity and the importance of the contribution to the subject area, has a very low validity and quality.